Techno-globalisation and labour sustainability in an era of the 4th Industrial revolution - Ukpere, Wilfred (Annals of Spiru Haret University. Economic Series, 2022)
Capitalism, as it is known is based on the concepts of competition, profit motive, private enterprises (self-interest) and scientific management. These key catalysts set the motion for capitalist expansion, exploration and exploitation. One notable area where capitalism has naturally done exceptionally well based on its characteristics, is within the domain of scientific management, which has spurred technological innovations as well as triggered techno-globalisation. In spite of several warning signs of the impact of techno-globalisation on the sustainability of labour, the world advanced into the 4th Industrial Revolutions, which is also driven by highly sophisticated technological advancements. The 4th IR has unique features, namely, smartphone takeover almost every aspect of business activity; knowledge generation is made possible through big data; robotics may likely replace many human routine activities in the workplace. The new trend will certainly lead to massive job losses as well as create new ones within the industry, which could have detriment effects for labour sustainability. However, some mechanisms have been postulated in this treatise to improve the status quo.